Comparison of three genomic DNA extraction methods to obtain high DNA quality from maize. Issue 1 (December 2017) - Abdel-Latif, Amani; Osman, Gamal
Abstract Background The world's top three cereals, based on their monetary value, are rice, wheat, and corn. In cereal crops, DNA extraction is difficult owing to rigid non-cellulose components in the cell wall of leaves and high starch and protein content in grains. The advanced techniques in molecular biology require pure and quick extraction of DNA. The majority of existing DNA extraction methods rely on long incubation and multiple precipitations or commercially available kits to produce contaminant-free high molecular weight DNA. Results In this study, we compared three different methods used for the isolation of high-quality genomic DNA from the grains of cereal crop, Zea mays, with minor modifications. The DNA from the grains of two maize hybrids, M10 and M321, was extracted using extraction methods DNeasy Qiagen Plant Mini Kit, CTAB-method (with/without 1% PVP) and modified Mericon extraction. Genes coding for 45S ribosomal RNA are organized in tandem arrays of up to several thousand copies and contain codes for 18S, 5.8S and 26S rRNA units separated by internal transcribed spacers ITS1 and ITS2. While the rRNA units are evolutionary conserved, ITS regions show high level of interspecific divergence and have been used frequently in genetic diversity and phylogenetic studies. In this study, the genomic DNA was then amplified with PCR using primers specific forITS gene. PCR products were then visualized on agarose gel. Conclusion The modified Mericon extraction method was found to be the most efficient DNA extraction method, capable to provide high DNA yields with better quality, affordable cost and less time.